2015
DOI: 10.3168/jds.2014-8052
|View full text |Cite
|
Sign up to set email alerts
|

Within-day variation and effect of acute stress on plasma and milk cortisol in lactating goats

Abstract: An experiment was carried out to study the effect of acute stress on cortisol concentration in goat milk (milk cortisol; MC) and its suitability for stress assessment. Additional variables studied were plasma cortisol (PC), blood glucose (BG), and somatic cell count (SCC). Ten goats free of mastitis at 2 mo of lactation were divided into 2 groups. One group of animals was exposed to acute stress (visual and auditory, but not physical, contact with a barking dog for 3 min) immediately before the 1000 h sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
6
12
1
2
Order By: Relevance
“…This is a difference compared to the effect of estrus, as this factor also produces an augmentation of SCC in primiparous goats (Mehdid et al, 2013). Romero et al (2015) did not find that acute stress for 5 minutes increased the SCC, but these authors only used primiparous IMI-free goats, which would coincide with what we observed in the present work. Other authors did not find that the stress induced by 45 minutes of transportation or by application of ACTH (Gaiato et al, 2012) affected SCC, but in both studies the distribution of goats according to parity number was not described and, therefore, we cannot know if it differs with our results.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This is a difference compared to the effect of estrus, as this factor also produces an augmentation of SCC in primiparous goats (Mehdid et al, 2013). Romero et al (2015) did not find that acute stress for 5 minutes increased the SCC, but these authors only used primiparous IMI-free goats, which would coincide with what we observed in the present work. Other authors did not find that the stress induced by 45 minutes of transportation or by application of ACTH (Gaiato et al, 2012) affected SCC, but in both studies the distribution of goats according to parity number was not described and, therefore, we cannot know if it differs with our results.…”
Section: Discussionsupporting
confidence: 74%
“…In ewes aged from to 6 years subjected to stress (isolation test for 10 minutes), Caroprese et al (2010) observed that SCC was higher in high-cortisol ewes than in low-cortisol ewes, but the differences were small (geometric means of 0.426 and 0.223 million cells/ml, respectively). Regarding the cortisol records in our experiment, we must specify that in order to rule out any possible circadian variation, the blood samples were taken at the same time each day, at 13:00 h, that is, at a time of day when the cortisol levels are low in non-stressed goats (Kokkonen et al, 2001;Romero et al, 2015). Two hypotheses could be formulated to explain the different behavior of the goats with three or more lactations compared to the younger goats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Verkerk et al [ 20 ] suggested that milk cortisol can reflect serum concentration only within 2–4 h after the response to acute stressors of lactating cows. Similarly, Romero et al [ 23 ] in goats reported a delay of 1.5 h between blood and milk cortisol increase in response to an acute stress. According to Fox et al [ 24 ], adrenal cortisol secretion is transferred from blood to milk rapidly (within 4 h), but in the absence of sustained activation of HPA axis the transfer rate declines and cortisol is diluted later, as a function of milk yield and milking interval.…”
Section: Discussionmentioning
confidence: 80%
“…This difference may reflect individual differences among cows [ 26 ]. Moreover, Romero et al (2015) and Verkerk et al (1998) suggested that milk cortisol content was influenced by the response to acute stressors in lactating cows and goats [ 27 , 28 ]. In addition, Sgorlon et al (2015) found that breed is a factor affecting milk cortisol concentration [ 18 ].…”
Section: Resultsmentioning
confidence: 99%